Selection Product Demulsifier To Improve Crude Oil Quality At Pertamina Pendopo Field - Putri Fanesa; Indah Dhamayanthie; Puji Astuti Ibrahim (Publikasi Indonesia, 2022)
PT Champion Kurnia Djaja Technologies' role is to produce oil field chemical products on a large scale and then used in applications in the petroleum industry. Petroleum is a fuel derived from fossils. Microorganisms living in the ocean. When these organisms die, their remains will settle to the bottom of the ocean and be covered in mud. Demulsifier or oil field is one of the specific chemicals to separate emulsions for example a mixture of water, petroleum. Product selection is done to analyze the quality of crude oil. The method used for analysis is the bottle test demulsifier in the laboratory by entering 40% water and 60% oil into saniglass and allowed to stand in the water bath and then injected with the chemical that has been observed, then 15, 30, 45, 60 minutes with Note the changes in the water drop, interface, and clarity of each sample, if not optimal, phase 2 testing will be carried out with the bottle test method and get the optimal West Benakat sample results by injecting chemical 1 + 3 the results are sharp interfaces, clear clarity and The BS&W is dry oil, while the Talang Akar sample is optimal in chemical 2 + 3 because the interface is sharp, the clarity is clear and the BS&W is dry oil.